BIAYA PRODUKSI DENGAN MENGGUNAKAN METODA ACTIVITY-BASED MANAGEMENT DALAM RANGKA MENGADAKAN PENINGKATAN TERHADAP EFISIENSI, KUALITAS DAN WAKTU - EDRIC KURNIADI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
With the diversified products, the company should consider using activity based costing method in calculating the production cost because this method will provide a more accurate calculation because it uses some of the basis for charging overhead. Activity based management will help management companies in addressing activities that do not have added value. Activity based management will help the management of the company to improve the quality of products produced, namely by providing analysis on existing activities and reduce errors that can occur in any activity so that the products will meet customer expectations.